A Longitudinal Study of S. aureus Infection in a National Cohort of Surgical Patients - O’brien, William J (Open Forum Infect Dis, 2019)
BACKGROUND: Postoperative infections are a common and often preventable complication of surgery. Staphylococcus aureus is a prevalent organism cultured in these infections and is associated with morbidity, mortality, and increased health care utilization. However, the long-term burden of S. aureus infection in surgical patients is not well studied. The purpose of this retrospective observational study was to assess the incidence, time trend, and burden of S. aureus infection up to 1 year after surgery. METHODS: We obtained manually reviewed data from the VA Surgical Quality Improvement Program (VASQIP) to identify surgeries in all major specialties. These were combined with laboratory microbiology and pharmacy data to identify pneumonia and infections of the urinary tract, surgical site, and blood. RESULTS: In the study population of 559 550 patients, S. aureus incidence decreased each year, from 2.1% in 2008 to 1.1% in 2015. Among these, incidence of methicillin-resistant S. aureus infection decreased from 0.7% to 0.4%, and methicillin-susceptible S. aureus decreased from 1.4% to 0.7%. S. aureus infection was associated with increased length of stay, emergency department utilization, inpatient admissions, and a 4-fold increase in mortality. CONCLUSIONS: This is one of the largest studies describing the long-term incidence of S. aureus in the surgical population of a national integrated health care system. We conclude that the burden of S. aureus infection extends well beyond the conventional 30-day postoperative window, and late infection should be included in assessing the effects of interventions.